Lipidômica e pré eclâmpsia - QUEIROZ, Lorena Lauren Chaves (2019)
Pre-Eclampsia (PE) is a potentially fatal pregnancy disorder whose pathogenesis is not fully understood. The origin of PE occurs very early in pregnancy, so many biophysical and biochemical markers have been proposed as predictors of preeclampsia. The objective of this study was to evaluate the lipid profile in detail in order to identify possible alterations, opening a new perspective for the understanding of the metabolic disorders experienced by pregnant women with PE, using a lipidic approach involving mass spectrometry. The serum lipid profile was analyzed in 40 pregnant women with preeclampsia and normal, and there was no difference between the two groups in relation to age, marital status, color, schooling, work or family income. When applying a lipidomic approach and mass spectrometry. Lipid species of the acylcarnitine type (C0, C3 and C5) showed significant changes (p <0.05). Lysophosphatidylcholines (lysoPC to C20: 4 and lysoPC to C28: 1) initially appear among the metabolites that presented statistically significant differences, but after the correction of multiple tests using Benjamini-Hochberg (BH) this significance was not maintained. However, it should be noted that lysoPC.a.C 16.1; 18.1; 20: 4 and 28: 1 showed increased concentrations in the preeclampsia groups. An increase in plasma levels of sphingomyelins C18.0, C18. 1, C20. 2, C24.1, C26.0 and C26.1 were observed in patients with preeclampsia. After multivariate analysis and BH application, the values were significant only for the metabolites SM C18: 0, SM C18: 1 and SM C26: 0. This study detected lipid alterations, especially in acylcarnitines in pregnant women with pre-eclampsia, as well as correlations with lysophosphatidylcholines, in addition to pregnant women with preeclampsia with elevation of Sphingomyelin, which may be associated with the process of pre-eclampsia. Such metabolites may assist in the knowledge of the genesis of preeclampsia, which may in the future be useful in the investigation of diseases associated with preeclampsia. Further studies are needed to confirm this data.